Molecular characterization of a phytoplasma associated with a commercial variety of Momordica charantia (Scientia Agricola, 2019)
Momordica charantia (bitter melon) presents two distinct types or varieties, known as wild type and commercial type. Plants of the wild type are hosts of a phytoplasma of the group 16SrIII-J, which is associated with a disease known as witches’ broom. However, this disease has not yet been reported in commercial bitter melon. Thus, symptomatic plants of the commercial type were analyzed in order to demonstrate the association between phytoplasmas and disease. In further assays, strains found in symptomatic plants of the commercial type were subjected to analysis of sequences of the secY gene to determine the extent of genetic diversity. Amplification of DNA fragments from genes 16Sr rRNA (1.2Kb) and secY (1.6Kb) revealed association of phytoplasma with symptomatic plants of the commercial type. Virtual Restriction Fragment Length Polymorphism (RFLP) analysis identified this phytoplasma as a member of the subgroup 16SrIII-J. Phylogenetic analysis showed that the phytoplasma was closely related to the representative of the 16SrIII-J subgroup. Molecular analysis indicated that the secY gene, in spite of the greater genetic variation compared with 16S rRNA gene, did not separate strains of the phytoplasma of the subgroup 16SrIII-J among those strains present in M. charantia.